2001
DOI: 10.4049/jimmunol.167.4.2157
|View full text |Cite
|
Sign up to set email alerts
|

E2A and HEB Activate the Pre-TCRα Promoter During Immature T Cell Development

Abstract: The pre-TCRα (pTα) is exclusively expressed in immature thymocytes and constitutes the pre-TCR complex with TCRβ, which regulates early T cell differentiation. Despite the recent identification of the pTα enhancer, the contribution of the promoter region, the direct DNA-protein interaction, and the regulation of such interaction along with T cell development have not been investigated. We analyzed the pTα promoter region and identified the critical elements for transcription of the pTα gene. The pTα promoter w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 29 publications
2
38
0
Order By: Relevance
“…In cotransfection experiments performed with EP180⌬E (from which the two E-boxes in the promoter region were deleted) or EmP180 (in which base substitutions were introduced in the three E-box sites in the enhancer region), luciferase activity could not be detected in the presence of E47. These observations confirm previous results demonstrating that E-box elements in both the enhancer and promoter regions are regulating the activation of the pT␣ gene (30,40).…”
Section: Resultssupporting
confidence: 82%
See 3 more Smart Citations
“…In cotransfection experiments performed with EP180⌬E (from which the two E-boxes in the promoter region were deleted) or EmP180 (in which base substitutions were introduced in the three E-box sites in the enhancer region), luciferase activity could not be detected in the presence of E47. These observations confirm previous results demonstrating that E-box elements in both the enhancer and promoter regions are regulating the activation of the pT␣ gene (30,40).…”
Section: Resultssupporting
confidence: 82%
“…Thus, the overexpression of E47, one of the two E2A proteins, and its binding to E-box sequences present in the promoter of the pT␣ gene resulted in increased transcription of this gene (27,30,40). In the present study, we first showed in transienttransfection experiments that the HTLV-1 Tax protein downregulated the activation of the pT␣ promoter mediated by the ectopic expression of E47.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Whether such a regulation occurs at the transcriptional level needs to be elucidated. Indeed, the pT␣ promoter has been recently described to carry E2A-and HEB-responsive E box cis-elements, although their functional characterization still requires full elucidation (23)(24)(25). Nevertheless, the transcriptional function of such bHLH E proteins has been described as inhibited by Notch signaling, either by way of the Ras pathway (26) or by the Notch-target HES-1 (27).…”
Section: Discussionmentioning
confidence: 99%